-2x-6=6x-14

Simple and best practice solution for -2x-6=6x-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-6=6x-14 equation:


Simplifying
-2x + -6 = 6x + -14

Reorder the terms:
-6 + -2x = 6x + -14

Reorder the terms:
-6 + -2x = -14 + 6x

Solving
-6 + -2x = -14 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-6 + -2x + -6x = -14 + 6x + -6x

Combine like terms: -2x + -6x = -8x
-6 + -8x = -14 + 6x + -6x

Combine like terms: 6x + -6x = 0
-6 + -8x = -14 + 0
-6 + -8x = -14

Add '6' to each side of the equation.
-6 + 6 + -8x = -14 + 6

Combine like terms: -6 + 6 = 0
0 + -8x = -14 + 6
-8x = -14 + 6

Combine like terms: -14 + 6 = -8
-8x = -8

Divide each side by '-8'.
x = 1

Simplifying
x = 1

See similar equations:

| 34a=2a+38 | | 4/5b-6=14 | | 3(x+7)-5=2x+7 | | -8(1+2p)=3p-8 | | (3x-6)(3x+7)= | | 0.3(X+15)+0.6(X+25)=33 | | -12x-17=-98 | | 34a=2a+4 | | u/12+(-8)=-8 | | v=x(10-2x)(3-2x) | | -3(x+7)=8 | | 49r^2=14r+8 | | 4+10s-2=9s+14-3s | | x^3/10-14x=2x^2/5 | | 3x-10-5x=-22 | | -1z+3.33=10 | | -d+12-3d=5d | | 8p+148p=15 | | -3=4a-a | | 2(x+5)=-x+2(x^2-5) | | 3y+9=48 | | -5.49+0.78=3.98 | | 3a*a=3+12a | | 1+6x=-5x+122 | | 1/4(18-a)=9.5 | | n+23=-24 | | 3v-v=14 | | -6(8-2a)=-92 | | 8-4=-7 | | x=3x+2.2(10-x) | | C=48m+0.99n | | 1+1=4z-10 |

Equations solver categories